2022
DOI: 10.32920/21440814.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Survival Effect in Memory: Does It Hold into Old Age and Non-Ancestral Scenarios?

Abstract: <p>The survival effect in memory refers to the memory enhancement for materials encoded in reference to a survival scenario compared to those encoded in reference to a control scenario or with other encoding strategies [1]. The current study examined whether this effect is well maintained in old age by testing young (ages 18–29) and older adults (ages 65–87) on the survival effect in memory for words encoded in ancestral and/or non-ancestral modern survival scenarios relative to a non-survival control sc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…54 Truong et al reported a lowcost and rapid sensor based on aptamer for the detection of S. aureus. 55 Bacteria induce the aggregation of silver nanoparticles at high salt concentration to produce color changes. DNA aptamer sensors can detect 10 5 CFU mL −1 bacteria in 20 min.…”
Section: Critical Review Analystmentioning
confidence: 99%
“…54 Truong et al reported a lowcost and rapid sensor based on aptamer for the detection of S. aureus. 55 Bacteria induce the aggregation of silver nanoparticles at high salt concentration to produce color changes. DNA aptamer sensors can detect 10 5 CFU mL −1 bacteria in 20 min.…”
Section: Critical Review Analystmentioning
confidence: 99%